كشف آيات القرآن ومتون الحديثكالمبادئ أحكام الأحوال الشخصية أجل لأدلة عقائديالشريعة عن تدوين - M. Gede Kurniawan; Abdul Wahab; Farikh Marzuqi Ammar (MAQASID, 2020)
ABSTRACTThe importance of knowledge to the proposition of an Islamic law is an absolute thing which is as a basis and evidence of the law, especially in AhwalusySyakhshiyyah law. From that term, a law in Islam has the power of law to be carried out accompanied by a belief without any doubt for Muslims where it is something scientific and principle. Then, this research is hoped to display the entire proposition both from Al-Quran or from Al-Hadith AhwalusySyakhshiyyah law to detail so that it appears in a codified form. The method in this study uses a qualitative method because the information obtained data has a qualitative paradigm, such as the results of the information obtained from the Holy Qur'an and the book of Jami'saheeh for each major narrator. Before searching the research, the researcher had the means previously found in the form of a digital version of the Qur'an 2.1, which was found in the application index from the arrangement of the legal arguments of AhwalusySyakhshiyyah, and for mutunAl-Hadith obtained from the HadithAhkam Subulus Salam for the composition of the arguments of his hadith which then denies each hadith from the authentic of each major narrator. The results of this research have been successful in detailing the legal arguments of the AhwalusySyakhshiyyah in each chapter in the form of a list of verse numbers and Surahs of the Quran and a list of Al-Hadist numbers which are then displayed lafadz texts from Al-Quran verses and mutunAl-Hadist. Furthermore, the conclusion of this research is that this research has succeeded in detailing the legal arguments of AhwalusySyakhshiyyah totaling 592 verses of the Quran and 385mutunAl-Hadith. So far, the researcher has a suggestion to later in further research to give more detailed details if it is possible from the legal arguments AhwalusySyakhshiyyah. Keywords: AhwalusySyakhshiyyah, Al-Hadith, Al-Quran, principles, verses, propositions, rules, codification, details.